A reversible bipolar WORM device based on AlOxNy thin film with Al nano phase embedded. (March 2017) - Zhu, W.; Li, J.; Zhang, L.; Hu, X.C.
Abstract: An Al-rich AlOx Ny thin film based reversible Write-Once-Read-Many-Times (WORM) memory device with MIS structure could transit from high resistance state (HRS, ∼10 11  Ω) to low resistance state (LRS, ∼10 5  Ω) by sweeping voltage up to ∼20 V. The first switching could be recorded as writing process for WORM device which may relate to conductive path are formed through the thin film. The conductive path should be formed by both Al nano phase and oxygen vacancies. Among of them, Al nano phases are not easy to move, but oxygen vacancies could migrate under high E-field or at high temperature environment. Such conductive path is not sensitive to charging effect after it formed, but it could be broken by heating effect, which may relate to the migration of excess Al ions and oxygen vacancies at high temperature. After baking LRS (ON state) WORM device at 200 °C for 2 min, the conductivity will decrease to HRS which indicates conductive path is broken and device back to HRS (OFF state) again. This phenomenon could be recorded as recovery process. Both writing and recovery process related to migration of oxygen vacancies and could be repeated over 10 times in this study. It also indicates that there is no permanent breakdown occurred in MIS structured WORM device operation. We suggest that this conductive path only can be dissolved by a temperature sensitive electro-chemical action. This WORM device could maintain at LRS over 10 5  s with on-off ratio over 4 orders.